Here's the picture of the circuit :

And here's my analysis so far :

First equation i get :

i1 = i2

(Vin - Vx)/R1 = (Vx - Vout)/R3

Second equation i get :

i4 = i5

(Vy - Vx)/R4 = Vx/R2

Third equation i get :

Iout = -i4 + i3

What makes me confuse that i've tried to make Second equation to get Vx = ........

Then, when i applied it to the first equation i got 3 variable, and i think that i made it even worst.

So, i'm now up to these ( second equation ) :

i4 = i5

(Vy - Vx)/R4 = Vx/R2

Vy/R4 = Vx/R2 + Vx/R4

Vy/R4 = Vx( (1/R2) + (1/R4) )

Then i don't know, whether to make Vx = ..... or Vy = ....

Thank you for your help.